Autoantibodies specific to D4GDI modulate Rho GTPase mediated cytoskeleton remodeling and induce autophagy in T lymphocytes. (April 2015) - Barbati, Cristiana; Alessandri, Cristiano; Vomero, Marta; Vona, Rosa; Colasanti, Tania; Vacirca, Davide; Camerini, Serena; Crescenzi, Marco; Pendolino, Monica; Truglia, Simona; Conti, Fabrizio; Garofalo, Tina; et al.
Abstract: T lymphocytes from patients with Systemic Lupus Erythematosus (SLE) display multiple abnormalities, including increased cell activation, abnormal cell death by apoptosis and impairment of autophagy pathway. In the present study we report the presence of specific antibodies to D4GDI, a small GTPase family inhibitor, in a significant percentage (46%) of SLE patient sera. We also found a significant association between the presence of these autoantibodies and hematologic manifestations occurring in these patients. Investigating the possible implication of anti-D4GDI autoantibodies in SLE pathogenesis or progression, we found that these antibodies were capable of binding D4GDI expressed at the lymphocyte surface and triggering a series of subcellular events, including Rho GTPase activation. These antibodies were also able to induce autophagy in T cells from both healthy donors and SLE patients, but only those negative to these antibodies. We can conclude that anti-D4GDI autoantibodies could be capable of triggering important responses in T cells such as cytoskeleton remodeling and autophagy pathway and that, in SLE patients, the chronic exposure to these specific autoantibodies could lead to the selection of autophagy-resistant T cell clones contributing to the pathogenesis of the disease. Highlights: Defective autophagy is a key actor in the pathogenesis of SLE. Autoantibodies to D4GDI are detected in sera from patients with SLE. Anti-D4GDI antibodies induce autophagy in T lymphocytes. Anti-D4GDI antibodies can select autophagy-resistant T cell clones in SLE patients. Anti-D4GDI antibodies can play a role in the pathogenesis of SLE.